Determination of Chemical Characterization of Foeniculum vulgare Mill Essential Oil Composition and its Toxicological Effects against Mosquito (Aedes caspius, Pallas, 1771) - Keffous Besma Safa; Aissaoui Lynda (Cutting Edge Research in Biology Vol. 3, 2023)
In this chapter, the essential oil (EO) of the aerial parts of Foeniculum vulgare Mill (Umbelliferae: Apiaceae) was extracted by hydro-distillation. Thereafter, its chemical composition was examined using gas chromatography (GC), and the profile was recognized using gas chromatography-mass spectrometry (MS).The toxicity of the EO was evaluated, after 24h of exposure time, against the fourth instar larvae of Aedes caspius and the sublethal and lethal concentrations, LC25, LC50 and LC90 values were estimated with their confidence limits and their values are 27.65, 37.76 and 70.40 \(μ\)l respectively. Based on the findings of the toxicity of F. vulgare EO, it can be concluded that the current aromatic plant species shown a considerable toxicological effect and may offer a suitable substitute for the control of mosquitoes. This finding opens up intriguing possibilities for its use in the creation of new sources of diverse larvicidal active substances for the management of mosquito vectors.